2015
DOI: 10.1016/j.idairyj.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of bovine lactoferrin potential as an anticancer agent

Abstract: Bovine lactoferrin (bLF) was shown to efficiently inhibit the growth of MCF-7, T-47D, MDA-MB-231 and Hs578T breast cancer cells in a concentration-dependent manner. However, apoptosis was only induced in MCF-7 cells, which was associated with the mitochondria membrane depolarisation and a decrease of Bcl-2 levels. bLF led to the cycle arrest of MCF-7 cells at G1/G0 phase, as well as a significant decrease in the expression of CDC25c. The possibility that the observed anticancer effects could be due to the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Bovine lactoferrin inhibited the growth of MCF‐7 breast cancer cell in a dose‐dependent manner by inducing apoptosis (Zhang and others ). Antitumor activities of bovine lactoferrin are also mediated through the retardation of angiogenesis (a multistep biological process for growth of new blood vessels from the pre‐existing vessels) and diminishing of endothelial cell proliferation (Shimamura and others ; Hoskin and Ramamoorthy ).…”
Section: Whey Protein‐derived Antitumor Peptidesmentioning
confidence: 98%
“…Bovine lactoferrin inhibited the growth of MCF‐7 breast cancer cell in a dose‐dependent manner by inducing apoptosis (Zhang and others ). Antitumor activities of bovine lactoferrin are also mediated through the retardation of angiogenesis (a multistep biological process for growth of new blood vessels from the pre‐existing vessels) and diminishing of endothelial cell proliferation (Shimamura and others ; Hoskin and Ramamoorthy ).…”
Section: Whey Protein‐derived Antitumor Peptidesmentioning
confidence: 98%
“…Also, the use of Lf as a coating agent due to its accumulation in breast tissue can be effective in targeting breast cancer 22 . In several studies, the anti-cancer activity of Lf is associated with the capacity of apoptosis through down-regulation of Bcl-2 mRNA 23 , along with up-regulation of the pro-apoptotic Bax and Caspase 3 mRNA 24 . Besides, Lf can result in targeted delivery of NP containing Doxo to tumor site 25 as well as an increase in the blood circulation time due to ability to escape from mononuclear phagocyte system (MPS) 26 and controlling drug release 2 , whereas, the anti-cancer mechanism of Lf ' is not fully understood.…”
mentioning
confidence: 99%
“…The increase in protein expression of Bcl-2, survivin and XIAP was observed in the apoptotic array. Studies have reported that bLf mediated apoptosis is mainly associated with the mitochondrial membrane depolarization and a decrease of Bcl-2 levels [60]. Moreover, increase in XIAP expression is known to confer resistance to apoptosis in cancer cells [61].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%